Project management for healthcare - Shirley, David, PMP (Boca Raton : CRC Press, 2011)
'A growing number of healthcare organizations are implementing project management principles to improve cost and service efficiencies. They are in desperate need of resources that clearly illustrate the project management needs of todays healthcare professional. Project Management for Healthcare fills this need. Using easy-to-follow language, it explains how the time-tested principles of project management can help maximize limited resources and ensure the highest possible quality of care. Exploring the discipline of project management from the perspective of the healthcare environment, the book dissects the project process and provides the tools and techniques required to successfully plan, execute, and control any healthcare-based project. From identifying stakeholders to constructing a project plan, this book covers the complete spectrum of project planning activities. Complete with chapter summaries, exercises, hints, review questions, and case studies, it illustrates applications across a range of healthcare settings. Explains how to utilize the project plan to execute projects within budget, schedule, and quality objectives Covers program management as it relates to healthcare Addresses the interaction between healthcare and information technology Presents best practices from the pharmaceutical and medical equipment industries that can easily be adapted to any helthcare setting Because most healthcare personnel will inevitably have to work with program management and need to interact with pharmaceutical companies and medical device manufacturers, the book provides an inside look at the processes and best practices used to bring products to market in these industries. Explaining how to adapt these processes to drive down costs and improve the quality of care in any healthcare setting, the book includes a case study of a fictitious medical facility that illustrates the proper application of the tools and techniques needed to manage healthcare projects effectively and efficiently'--Provided by publisher.
'Preface I was a healthcare professional. My first'real' job after graduating from college was as a licensed health inspector, then as a licensed health officer, and finally as a health administrator for a small town with a population of about 15,000 people. It was there that I became an accidental or incidental project manager. Until recently, project management was an'accidental profession.' Few started out as project managers. They were usually something else and either were handed a project to undertake, or suggested an enhancement to an existing process, procedure, or product, and were told to'run with it.' Either way, their primary job was doing something else. As the health administrator, I was responsible for the animal control program in my town. Because I had a full-time animal control warden and an animal control van, the town suggested I offer those services to other local municipalities to generate income to be able to expand my program. Two of the abutting towns agreed and signed a contract with our Board of Health. Part of that agreement was to pick up stray dogs and cats. It immediately became clear that we needed a place to house the animals'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Health services administration; Project management; Delivery of Health Care -- organization & administration; Health Services Administration; Management information systems; Organizational Innovation